Exploring the Complementary Roles of Social Networks and Search Engines - Morris, Meredith Ringel; Teevan, Jaime (2012 Human-Computer Interaction Consortium Workshop (HCIC), Asilomar, CA, 2012)
The Web has become an important information repository; often it is the first source a person turns to with an information need. One common way to search the Web is with a search engine. However, it is not always easy for people to find what they are looking for with keyword search, and at times the desired information may not be readily available online. An alternative, facilitated by the rise of social media, is to pose a question to one's online social network. We present a series of studies that have explored the differences in the types of questions that people choose to explore via asking their networks versus using search engines, and compare the speed, quality, and quantity of answers discovered using these two methods. We then discuss the implications of these findings for next generation information-seeking technologies that integrate the benefits of using both search engines and social networks. We believe there is an pportunity for tools to help people’s friends collaborate with algorithmic information retrieval tools to produce better answers than either approach might identify alone.